2011
DOI: 10.1042/cbi20090459
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical factors influencing the shikonin derivatives production in cell suspension cultures ofArnebia euchroma(Royle) Johnston, a medicinally important plant species

Abstract: Cell suspension cultures of Arnebia euchroma were raised from in vitro leaf-derived friable callus on liquid MS [Murashige and Skoog] medium supplemented with BAP (6-benzylaminopurine) (10.0 μM) and IBA (indole-3-butyric acid) (5.0 μM). A two-stage culture system was employed using growth and production medium for cell biomass and shikonin derivatives, respectively. Factors such as light, temperature, sucrose and pH (hydrogen ion concentration) were studied to observe their effect on the shikonin derivative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
1
39
0
3
Order By: Relevance
“…The shikonin derivatives in the organic phase obtained being recovered as a blue aqueous solution by using 1 ml of 2.5 % KOH. Absorbance of samples was recorded at 620 nm using spectrophotometer (Hussain et al 2012, 2011). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shikonin derivatives in the organic phase obtained being recovered as a blue aqueous solution by using 1 ml of 2.5 % KOH. Absorbance of samples was recorded at 620 nm using spectrophotometer (Hussain et al 2012, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Owing to these properties, genus Arnebia is over-exploited and therefore, placed under the category of critically endangered species. The plants are very difficult to cultivate through conventional agriculture (possess third level of difficulty in seed germination) (Malik et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites produced from cyanobacteria are found to be antibacterial, antifungal, antialgal, anticancerous and antimalarial with many more activitys [3,4] . Microbial productions of metabolites are greatly influenced by factors such as pH, temperature, and light intensity [5][6][7][8] . However, species specificity of secondary metabolites is well established [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that vinblastine and vincristine can be semi-synthesized by using catharanthine and vindoline as precursors (Ishikawa et al 2009). For several years, plant tissue culture has been considered as a promising biotechnological approach to improve the secondary metabolites production (Malik et al 2011(Malik et al , 2014. Organized cultures, especially transgenic hairy root cultures induced by Agrobacterium rhizogenes, represent a reliable alternative to undifferentiated tissue cultures, such as cell suspensions, for the production of valuable secondary metabolites (Mujib et al 2012;Malik et al 2016).…”
Section: Introductionmentioning
confidence: 99%